Pentingnya Penanaman Nilai – Nilai Pancasila Dalam Pendidikan Untuk Membangun Karakter Bangsa - Dinda Zahra Rama Sabila; Elgy Sundari; Muhamad Yanuar Alfaridzi; Muhammad Jilan Satria; Muhamad Abdul Azis; Muhammad Naufal Fadlurrahman6; Syahdan Alfiansyah; Yayang Furi Furnamasari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Pancasila Education plays an important role in shaping the character of Indonesia's young generation amidst the challenges of globalization and technological advancement. The purpose of this research is to understand how Pancasila education can help the younger generation comprehend and internalize the values of Pancasila in their daily lives. The method used is qualitative analysis with a literature study approach. Data were collected from various literary sources, such as books, scientific journals, articles, and other reliable sources. The research results show that more than 70% of the young generation in Indonesia experience difficulties in understanding and applying Pancasila values. The lack of instilling Pancasila values in the educational curriculum has led to a decline in morals and ethics among the younger generation. Therefore, systematic, innovative, and contextual efforts in Pancasila education are needed to attract the interest of the younger generation and help them deeply understand Pancasila values. The conclusion of this research is that Pancasila education is crucial for the young generation of Indonesia to build a strong and moral national character.